Sensory descriptive and comprehensive GC-MS as suitable tools to characterize the effects of alternative winemaking procedures on wine aroma. Part II: BRS Rubea and BRS Cora - Machado de Castilhos, Mauricio Bonatto; Del Bianchi, Vanildo Luiz [UNESP]; Gomez-Alonso, Sergio; Garcia-Romero, Esteban; Hermosin-Gutierrez, Isidro (Elsevier B.V., 2020)
The present manuscript assessed the volatile and sensory profiles of BRS Rubea and BRS Cora wines elaborated from traditional, grape pre-drying and submerged cap winemaking. The wines contained a higher concentration of acetates (257 mg L-1 to 547 mg L-1) and ethyl and methyl esters (183 mg L-1 to 456 mg L-1 ) in comparison with Vitis vinifera wines. PCA was applied (explaining 68.43% of the total variance), and the higher concentration of ethyl decanoate and ethyl octanoate, diethyl succinate, hydroxylinalool, and 2-phenyl ethanol was responsible for describing the BRS Rubea wines as fruity/foxy. They also presented an intense jam note, probably due to their higher concentration of syringol and guaiacol. BRS Cora wines exhibited a vegetal note, possibly due to their higher concentration of 1-hexanol and cis-3-hexenol. Wines from pre-dried grapes presented higher concentration of furfural, assuming a bitter/burned almond aroma. Alternative winemaking accounted for suitable changes in wine aroma, enhancing wine quality.
Keywords: Wine; Drying; Submerged cap; Volatile compounds; Sensory descriptive analysis; Non-Vitis vinifera